Chemotherapy-induced neuropathy: incidence, natural history, measurement, prevention, and treatment - Loprinzi, Charles (Henry Stewart Talks, 2016)
Chemotherapy-induced neuropathy (CIN) causative agents, The history of CIN, Measurement methods for CIN, Prevention options for CIN, Available CIN treatments and recommendations